The role of English agronyms in ethnolinguoculture - Xakimbayeva, Ozoda (The Lingua Spectrum, 2025)
Modern society cannot be imagined without geography. Toponyms are an integral element of the development of society. Their accumulation in a certain territory is the result of centuries-old folk creativity. Despite the fact that toponyms have been sufficiently studied in linguistics today, it would be an understatement to say that there are enough innovations in the field as a result of the emergence of new place names and the replacement of old names with new ones. In this article, the author discusses the role of agronomists, characteristic of English culture, in the ethnolinguistic culture.